1992
DOI: 10.1049/ip-g-2.1992.0015
|View full text |Cite
|
Sign up to set email alerts
|

Electrical capacitance tomography for flow imaging: system model for development of image reconstruction algorithms and design of primary sensors

Abstract: A software tool that facilitates the development of image reconstruction algorithms, and the design of optimal capacitance sensors for a capacitance-based 12-electrode tomographic flow imaging system are described. The core of this software tool is the finite element (FE) model of the sensor, which is implemented in OCCAM-2 language and run on the Inmos T800 transputers. Using the system model, the in-depth study of the capacitance sensing fields and the generation of flow model data are made possible, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
266
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(271 citation statements)
references
References 5 publications
0
266
0
5
Order By: Relevance
“…The implemented LBP reconstruction algorithm (Xie et al, 1992) is described by the following equation.…”
Section: Q(x Y) B(x Y)mentioning
confidence: 99%
See 1 more Smart Citation
“…The implemented LBP reconstruction algorithm (Xie et al, 1992) is described by the following equation.…”
Section: Q(x Y) B(x Y)mentioning
confidence: 99%
“…The technique tends to bias toward splitting the grey level histograms into equal halves (Kapur, 1989). However, improvement in higher gas concentration ranges can be done by incorporating the truncation mechanism of Xie et al (1992) as already demonstrated elsewhere (Mwambela and Johansen, 2001). It is difficult to minimize distortions in lower gas concentration ranges because of the following reason.…”
Section: On-line Dynamic Measurementsmentioning
confidence: 99%
“…Problems issued from diffractive or scattering systems can be usually solved by means of algorithms based on moment and pseudo inversion methods (Caorsi et al [5]; Chiu et al [6]). Problems issued from electric sensing systems can be frequently treated with several back-projection methods (Huang et al [7]; Xie et al [8]) and by means of iteration algorithms based on optimization techniques (Isaksen & Nordtvedt [9]), perturbation methods (Kim & Woo [10]; Yorkey et al [11]) or the NewtonRaphson method (Yorkey et al [12]; Abdullah et al [13]). …”
Section: Tomographic Imagingmentioning
confidence: 99%
“…In addition, the algorithms available for image reconstruction assume in general the electrical field to be static and two-dimensional. Calculation results may consequently exhibit some over and undershooting as for instance void fractions above 100% and under 0% (Xie et al [8]). In the same way, 3D effects lead to the presence of "phantom objects" in the reconstructed images, when the flow configuration is not bidimensional (Peytraud [16]).…”
Section: Tomographic Imagingmentioning
confidence: 99%
“…Some reconstructions algorithms have been proposed to address the problem [16][17][18][19][20][21][22][23][24]. Others have improved images from LBP by further preprocessing the images using different approaches such as filtering [25], segmentation [26] and curve fitting [27].…”
Section: Introductionmentioning
confidence: 99%